Does learner strategy training make a difference? - Nunan, David (Lenguas Modernas, 2017)
This study investigated the effects of strategy training on four key aspects of the learning process, namely student motivation, students' knowledge of strategies, the perceived utility of strategies, and the actual deployment of strategies by students. The study took the form of an experiment in which sixty first-year undergraduate students at the University of Hong Kong were randomly assigned to control and experimental groups. Both groups took part in that same language program. In addition, the experimental groups were systematically trained in fifteen learning strategies. Results of the study indicated significant differences in three of the four areas investigated. The experimental groups significantly outperformed the control groups on motivation, knowledge, and perceived utility. There was no significant difference in the area of deployment. Analysis of results on individual strategies revealed that strategy training was neither uniform nor consistent across all strategies. In the concluding section of the paper the theoretical and pedagogical implications of the study are set out and discussed.